Terms integrating status and integration in education An analytical study - Boufes, Abd alhamid (Milev Journal of Research and Studies, 2021)
This research deals with the terms integrating status and inclusion by addressing their concept in linguistic dictionaries as well as studies of researchers in the education, pedagogy and didactics, with reference to the various designations of integrating situations, types and characteristics of inclusion. Where the pedagogy of integration was one of the contemporary approaches to education that raised problems in its relationship to competence. The research concludes with the link that exists between the two linguistic and idiomatic concepts for status and integration, as well as considering inclusion as a criterion for achieving competency.